A comparison of the changes in serum lactate between surgical repair and transthoracic device closure of ventricular septal defects in pediatric patients - Huang, Jiang-Shan; Chen, Yu-Kun; Lin, Shi-Hao; Chen, Qiang; Cao, Hua; Zheng, Yi-Rong (Frontiers in Cardiovascular Medicine, 2023)
Objective The purpose of this study was to compare the changes in serum lactate between surgical repair and transthoracic device closure of ventricular septal defects (VSDs) in pediatric patients. Methods This study was a retrospective analysis, and 314 pediatric patients with simple VSD from October 2019 to October 2021 were selected. The patients were divided into the S group (surgical repair) and the D group (transthoracic device closure). The serum lactate value at ICU admission and 6 h after operation, as well as the highest serum lactate value were collected, and the 6-h serum lactate clearance rate was calculated. Result Through propensity score matching, 43 pairs of cases were successfully matched. Compared with the S group, the D group had a shorter operation duration, ventilation duration, and ICU duration, as well as a lower drainage volume and total hospitalization cost. There was no significant difference between the two groups in the initial and highest serum lactate values after VSD closure, while the 6-h serum lactate value in the D group was significantly lower than that in the S group, and the 6-h serum lactate clearance rate in the D group was five times faster than that in the S group. In addition, the 6-h serum lactate clearance rate in the S group was mainly related to the operation time, CPB time, and ventilation time, while the 6-h serum lactate clearance rate in the D group was only related to the operation time. Conclusion The initial and highest serum lactate levels were not significantly different between surgical repair and transthoracic device closure of VSD, but the 6-h serum lactate clearance rate of device closure was five times faster than that of surgical repair.